Answered

At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

A function [tex]$f[tex]$[/tex] is given by [tex]$[/tex]f(x)=3x$[/tex]. Find [tex]\left(f \circ f^{-1}\right)(3)[/tex].

A. [tex]\square[/tex] 9
B. [tex]\square[/tex] 6
C. [tex]\square[/tex] 3
D. [tex]\square[/tex] 1


Sagot :

To find \((f \bullet f^{-1})(3)\), we need to follow a few steps:

1. Determine the inverse function \(f^{-1}(x)\) of \(f(x) = 3x\):
- Given the function \(f(x) = 3x\), we want to find the inverse function \(f^{-1}(x)\).
- To find the inverse, we start with the equation \(y = 3x\), and solve for \(x\):
[tex]\[ y = 3x \implies x = \frac{y}{3} \][/tex]
- Therefore, the inverse function is \(f^{-1}(x) = \frac{x}{3}\).

2. Calculate \(f^{-1}(3)\):
- Using the inverse function \(f^{-1}(x) = \frac{x}{3}\), we substitute \(x = 3\):
[tex]\[ f^{-1}(3) = \frac{3}{3} = 1 \][/tex]

3. Calculate \(f(f^{-1}(3))\):
- We found that \(f^{-1}(3) = 1\). Now, substitute this back into the original function \(f(x) = 3x\):
[tex]\[ f(f^{-1}(3)) = f(1) = 3 \cdot 1 = 3 \][/tex]

Thus, \((f \bullet f^{-1})(3) = 3\).

The correct answer is:
C. [tex]\( \boxed{3} \)[/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.